The Calculation and Grouping of Financial Rational Indicators - Mackevičius, Jonas (Ekonomika, 2006)
Financial rational indicator is the relation of two or more absolute indicators. Rational indicator retrieved from comparing two or more absolute indicators. Financial rational indicator is much more informative than absolute one, it enables the person to evaluate the research object at a different angles.Financial rational indicators are most important when compared with: 1) the firm’s last period indicators, 2) with forecasted parameter indicators, 3) with other companies in the same business field, 4) with the indicators of main market competitors, 5) with aggregated country economy indicators.When analyzing financial rational indicators it is important to be sure that indicators reliability depends on the actual information, which has been used to calculate them. That is why before calculating and analyzing financial indicators you have to check all the financial reports carefully and thoroughly (profit (loss), balance sheet, own capital changes, cash flow and explanatory notes), also to make sure that forms of reports indicators are coordinated with one another.Since at lot of financial rational indicators can be calculated from financial reporting, thus necessary to systematize them, and integrate them in to certain groups. Indicator integration into homogeneous groups can ease analyst’s and audit tasks, it is also beneficial for information users to select the more suitable indicators and opt for better operational and perspective indicators in decision making.After performing financial rational indicator integration in foreign authors works the conclusions could be made:1. Names of financial rational indicators groups differ. Most commonly used are liquidity and profitability indicators groups.2. Sequence of financial rational indicators groups positioning differs. Some authors start analyzing financial indicators from liquidity, some from profitability, and other from risk, etc.3. The number of financial rational indicators groups also differs. Some authors distinguish two groups, some five or six.4. The number of financial rational indicators in the actual group also differs. For example some authors assign three, four, some twelve or even fourteen indicators to profitability indicator groups. The reasons for financial rational indicator groups, and indicator name differences could be explained:1) In different countries financial reporting forms vary, some balance sheet, profit (loss), cash flow statements clauses are named differently;2) Authors usually analyze the particular economics field financial reports, specific financial indicators reflect that particular field’s work characteristics.3) In some English speaking countries some indicator names were historically developed, that was the cause of the main name differences.4) Author’s professional competence and their representation of particular sciences: Accounting, Finance, Management, Statistics, Financial Analysis etc.5) Financial rational indicators are intended for different groups and users: investors require information which would differ from the information required by the suppliers, banks and other users or institutions.Foreign authors financial rational indicators classification into groups and their actual naming and calculation methods had an impact on Lithuanian authors and still has up to this day. Different number of financial rational indicators groups is distinguished and named differently by Lithuanian authors, this causes a great confusion to different information users, firstly students, lecturers, accountants, auditors, finance analysts.In order to satisfy need for general information about customer business activities, it is recommended to separate financial rational indicators into three groups: indicators that evaluate enterprise’s financial position, measure performance results and cash flows.